2018
DOI: 10.1139/apnm-2018-0161
|View full text |Cite
|
Sign up to set email alerts
|

The role of the nervous system in neuromuscular fatigue induced by ultra-endurance exercise

Abstract: Ultra-endurance events are not a recent development but they have only become very popular in the last 2 decades, particularly ultramarathons run on trails. The present paper reviews the role of the central nervous system in neuromuscular fatigue induced by ultra-endurance exercise. Large decreases in voluntary activation are systematically found in ultra-endurance running but are attenuated in ultra-endurance cycling for comparable intensity and duration. This indirectly suggests that afferent feedback, rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…Moreover, it has been shown that mountain running endurance events have a high impact on peripheral fatigue, reducing muscle function and performance [ 3 , 20 , 58 ]. Specifically, changes in excitation–contraction (E-C) coupling failure and neuromuscular propagation reduction may contribute to a decrease in maximal force production [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been shown that mountain running endurance events have a high impact on peripheral fatigue, reducing muscle function and performance [ 3 , 20 , 58 ]. Specifically, changes in excitation–contraction (E-C) coupling failure and neuromuscular propagation reduction may contribute to a decrease in maximal force production [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that mountain running endurance events have a high impact on peripheral fatigue, reducing muscle function and performance [ 3 , 20 , 58 ]. Specifically, changes in excitation–contraction (E-C) coupling failure and neuromuscular propagation reduction may contribute to a decrease in maximal force production [ 58 ]. In the same line, downhill running induced eccentric contractions and EIMD are related to so-called low-frequency fatigue (LFF), which has been closely associated with E-C coupling failure and, as explained, with muscle force reduction [ 20 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain glycogen is chiefly located in these glial cells and it decreases with extensive and prolonged exercise ( Matsui et al, 2012 , 2017 ). However, it is still unknown whether UE running induces altered glial activity as well as modifies antioxidant defense mechanisms when associated with high-volume running training ( Jastrzȩbski et al, 2015 ; Rama et al, 2015 ; Knechtle and Nikolaidis, 2018 ; Millet et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current discussion on the negative effects of high-volume and UE on runner health ( Knechtle and Nikolaidis, 2018 ; Millet et al, 2018 ), and the scarcity of knowledge about these effects in locomotion-related brain regions has motivated the present study. We hypothesized that rodent cerebellar resilience to oxidative injuries may be reduced after high-volume training, regardless of the exhaustion test simulating UE running.…”
Section: Introductionmentioning
confidence: 99%